Gastrointestinal parasite infections in Nepalese Gurkha recruits arriving in the United Kingdom from 2012-2020. - William D Nevin; Jayne Jones; Donna Tupper; James A T Dunbar; Duncan Wilson; David Ross; Stephen Woolley; James Dodd; Jason Biswas; Lucy Lamb; Nicholas J Beeching; Matthew K O'Shea; et al. (Public Library of Science (PLoS), 2024)
Background Gastrointestinal parasite (GIP) infections are a major cause of global morbidity, infecting hundreds of millions of people each year and potentially leading to lifelong infection and serious complications. Few data exist on screening for GIP infections in migrants entering the UK or on the current performance of different traditional diagnostic approaches. This study aimed to describe the prevalence of GIP infections in Nepalese Gurkha recruits screened on arrival in the UK. Methodology/principal findings We present a retrospective analysis of data from screening male adults (18-21 years) who arrived in the UK from Nepal between 2012 and 2020. Three separate faecal samples were obtained from participants at weekly intervals and processed for formalin-ethyl acetate (FEA) concentration/light microscopy and charcoal culture. Serum samples were analysed for IgG antibodies to Strongyloides stercoralis by ELISA. Results were available from 2,263 participants, of whom 463 (20.5%, 95% CI 18.8%-22.2%) had a positive diagnostic test for at least one GIP infection. A total of 525 potential infections were identified. Giardia duodenalis was most common (231/2263, 10.2%), followed by S. stercoralis (102/2263, 4.5%), and hookworm species (86/2263, 3.8%). Analysis (microscopy and culture) of the initial stool sample diagnosed only 244/427 (57.1%) faecally identified pathogens, including 41/86 (47.7%) hookworm infections. The proportion of participants infected with any GIP showed a downward trend over the study period. Log-binomial regression showed risk of infection decreasing by 6.1% year-on-year (95% CI 3.2% - 9.0%). This was driven predominantly by a fall in hookworm, S. stercoralis and Trichuris trichiura prevalence. Conclusions/significance The level of potentially pathogenic GIP infection in young Nepalese men migrating to the UK is high (20.5%) and requires a combined diagnostic approach including serology and analysis of multiple stool samples incorporating specialised parasitological methods. Advances in molecular approaches may optimise and simplify the intensive screening strategy required.